163k views
5 votes
I NEED HELP ASAP! PLS! <3

I NEED HELP ASAP! PLS! <3-example-1
User Suzzette
by
5.4k points

1 Answer

5 votes

Answer:

a = - 1 [m/s²]

Step-by-step explanation:

To solve this problem we must use the following equation of kinematics.


v_(f) = v_(o) +(a*t)

where:

Vf = final velocity = 0 (velocity at 10 seconds)

Vo = initial velocity = 4 [m/s]

a = desacceleration [m/s²]

t = time = 4 [s]

From the graph, we can deduce that between the second 10 and the second 6 there are (10-6) = 4 seconds difference.

In the second 6, the velocity is 4 [m/s]

0 = 4 + (a*4)

4*a = -4

a = - 1 [m/s²]

User Giorgos Betsos
by
5.4k points